2007
DOI: 10.2320/matertrans.mra2007043
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bismuth Sodium Titanate Fine Particles with Different Shapes by the Gel-Sol Method

Abstract: Polycrystalline spherical Bi 0:5 Na 0:5 TiO 3 (BNT) particles with narrow size distributions were obtained by the gel-sol method, where the precursory gel was composed of BiX 3 (X ¼ OH, NO 3 ), NaOH, and stable Ti 4þ complex which was prepared by mixing Ti(i-C 3 H 7 O) 4 with triethanolamine to inhibit the uncontrolled hydrolysis in aqueous solution. The resulting morphology was readily controlled as single-crystalline rod-like and tubular shapes with the simple tuning of the Bi/Ti molar ratios in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Decrease in pH init induces the formation of Bi 2 Ti 2 O 7 . 19) In the present study, the main target is to completely prevent the formation of bismuth metal particles, which was observed in our previous system. 19) Such a bismuth metal formation must be formed through the reduction of bismuth ions by triethanolamine used as a complexing agent of metal ions in our previous studies.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Decrease in pH init induces the formation of Bi 2 Ti 2 O 7 . 19) In the present study, the main target is to completely prevent the formation of bismuth metal particles, which was observed in our previous system. 19) Such a bismuth metal formation must be formed through the reduction of bismuth ions by triethanolamine used as a complexing agent of metal ions in our previous studies.…”
Section: Resultsmentioning
confidence: 80%
“…32) We have been applying this method to the preparation of various shapes of BNT fine particles controlled in their size and shape, such as sphere, rod, and nanotube. 19) However, the problem at stake was the by-production of bismuth metal during this process. This serious problem of undesired change in Na/Bi/Ti ratio of as-prepared product as well as the contamination of Bi metal in ceramic materials causes unexpected trouble such as current leak and breakdown of the ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,43) Actually, our previous studies obtaining complex perovskite fine particles such as BNT showed that initial pH strongly influenced to the crystal structure and shape of the particles. 21,22) In this regard, the effect of initial KOH concentrations was investigated on the formation rate and the morphology of KN fine particle. Here, the hydrothermal synthesis was carried out by following two-step aging: 100 C for 24 h and 250 C for 3 h. The two-step aging process is an efficient procedure for the preparation of monodispersed fine particles in the Gel-Sol method.…”
Section: Effect Of Koh Concentration On Formation Ofmentioning
confidence: 99%
“…17,18) Recently, utilization of such welldefined metal oxide powders as precursors for piezoelectric ceramics has received much attention, because high performance ceramics close to a morphotropic phase boundary have been obtained by texture-treatment 19) or template grain growth method 20) using them. In our previous studies, we have developed preparation technique of shape-controlled bismuth sodium titanate (BNT) 21,22) and bismuth potassium titanate (BKT) 22) fine particles with complex perovskite-type structures from aqueous solutions. Since BNT and BKT, one of the most promising alternatives to PZT, their fine particles controlled in their size and shape, such as sphere, cube, rod, and nano-tube are readily prepared by the Gel-Sol method.…”
Section: Introductionmentioning
confidence: 99%